2014
DOI: 10.1007/s12033-014-9782-9
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant DNA Technology for Melanoma Immunotherapy: Anti-Id DNA Vaccines Targeting High Molecular Weight Melanoma-Associated Antigen

Abstract: Anti-idiotypic MK2-23 monoclonal antibody (anti-Id MK2-23 mAb), which mimics the high molecular weight melanoma-associated antigen (HMW-MAA), has been used to implement active immunotherapy against melanoma. However, due to safety and standardization issues, this approach never entered extensive clinical trials. In the present study, we investigated the usage of DNA vaccines as an alternative to MK2-23 mAb immunization. MK2-23 DNA plasmids coding for single chain (scFv) MK2-23 antibody were constructed via the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…Despite the promising clinical results, MK2-23 never reached clinical application as a therapy due to standardization issues and safety concerns linked to its administration together with the adjuvant Bacille Calmette-Guerin (BCG), deemed necessary for triggering effective adaptive immune responses ( 94 ). Further approaches to overcome those issues included fusing MK2-23 to human IL-2 ( 94 ) or utilizing DNA vaccines encoding MK2-23 scFv ( 95 ). In a phase I clinical trial, another anti-idiotypic antibody, MF11-30, induced complete remission in one advanced melanoma patient as well as conferred minor survival benefits in three other patients with advanced melanoma whilst no toxicities were reported as a part of Ref.…”
Section: Cspg4 As a Target For Antibody Therapies In Cancermentioning
confidence: 99%
“…Despite the promising clinical results, MK2-23 never reached clinical application as a therapy due to standardization issues and safety concerns linked to its administration together with the adjuvant Bacille Calmette-Guerin (BCG), deemed necessary for triggering effective adaptive immune responses ( 94 ). Further approaches to overcome those issues included fusing MK2-23 to human IL-2 ( 94 ) or utilizing DNA vaccines encoding MK2-23 scFv ( 95 ). In a phase I clinical trial, another anti-idiotypic antibody, MF11-30, induced complete remission in one advanced melanoma patient as well as conferred minor survival benefits in three other patients with advanced melanoma whilst no toxicities were reported as a part of Ref.…”
Section: Cspg4 As a Target For Antibody Therapies In Cancermentioning
confidence: 99%
“…59) Attempts to address these concerns involved fusing MK2-23 with human IL-2 59) or creating deoxyribonucleic acid (DNA) vaccines that encode MK2-23 scFv. 60) In 1990, Mittelman et al 61) presented their findings from two clinical trials on the use of the mouse-derived mAb, MF11-30, for treating stage IV malignant melanoma. This mAb, which mimics human HMW-MAA, was administered to patients subcutaneously at varying doses.…”
Section: Anti-idiotypic Antibodies (Anti-ids) Tar-mentioning
confidence: 99%
“…The human high molecular weight melanoma-associated antigen (HMW-MAA) is a cell surface proteoglycan expressed in more than immunization (Barucca et al, 2014). It has been also shown that the plasmid DNA vaccine encoding for streptococcus pyogenes EMM55 protein (pAc/emm55) could increase the IgG antibodies and immune responses in horses with metastatic melanoma.…”
Section: The Universal Mutational Genesmentioning
confidence: 99%